Severe acute respiratory infections caused by 2009 pandemic influenza A (H1N1) among American Indians—southwestern United States, May 1–July 21, 2009. Issue 6 (30th May 2013) - Suryaprasad, Anil; Redd, John T.; Hancock, Kathy; Branch, Alicia; Steward‐Clark, Evelene; Katz, Jacqueline M.; Fry, Alicia M.; Cheek, James E.
<x xml:space="preserve">Abstract</x> Background During April–July 2009, U.S. hospitalization rates for 2009 pandemic influenza A (H1N1) virus (H1N1pdm09) infection were estimated at 4·5/100 000 persons. We describe rates and risk factors for H1N1pdm09 infection among American Indians (AIs) in four isolated southwestern U.S. communities served by the Indian Health Service (IHS). Methods We reviewed clinical and demographic information from medical records of AIs hospitalized during May 1–July 21, 2009 with severe acute respiratory infection (SARI). Hospitalization rates were determined using denominator data provided by IHS. H1N1pdm09 infection was confirmed with polymerase chain reaction, rapid tests, or convalescent serology. Risk factors for more severe (SARI) versus milder [influenza‐like illness (ILI)] illness were determined by comparing confirmed SARI patients with outpatients with ILI. Results Among 168 SARI‐hospitalized patients, 52% had confirmed H1N1pdm09 infection and 93% had >1 high‐risk condition for influenza complications. The H1N1pdm09 SARI hospitalization rate was 131/100 000 persons [95% confidence interval (CI), 102–160] and was highest among ages 0–4 years (353/100 000; 95% CI, 215–492). Among children, asthma (adjusted odds ratio [aOR] 3·2; 95% CI, 1·2–8·4) and age <2 years (aOR 3·8; 95% CI, 1·4–10·0) were associated with H1N1pdm09 SARI‐associated hospitalization, compared with outpatient ILI. Among adults, diabetes (aOR 3·1; 95% CI, 1·5–6·4) was associated with hospitalization after controlling for obesity. Conclusions H1N1pdm09 hospitalization rates among this isolated AI population were higher than reported for other U.S. populations. Almost all case patients had high‐risk health conditions. Prevention strategies for future pandemics should prioritize AIs, particularly in isolated rural areas.